RESPON ORANG TUA TERHADAP SISWA YANG DIWAJIBKAN VAKSINASI COVID-19 DI SD IT MUTIARA HATI PAYAKUMBUH - Zharifah "; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to determine the response of parents to students who are required to be vaccinated against Covid-19 at SD IT Mutiara Hati Payakumbuh. The responses given by parents (respondents) were of course different. The response can be seen from three aspects including cognitive response, affective response, conative response. This research is located in the Subang Batuang Village, Payakumbuh City, West Sumatra Province. The method used in this research is descriptive quantitative method. This study has 427 populations. This study used the slovin formula to determine the sample and obtained 81 samples. The sampling technique in this study used proportional random sampling. Data collection was carried out through primary data using questionnaires and secondary data. The results of this study, the health team together with the school principal and teachers held outreach through meetings and outreach through banners and then the responses that emerged from the parents of students could be seen that most parents supported the covid-19 vaccination program for children at SD IT Mutiara Hati Payakumbuh. Key words: Parents Response, Covid-19 Vaccination, Socialization